Tumor size and Fuhrman grade further enhance the prognostic impact of perinephric fat invasion and renal vein extension in T3a staging of renal cell carcinoma. (18th October 2016) - Chen, Kenneth; Lee, Bing Long; Huang, Hong Hong; Tan, Benjamin Yongcheng; Lee, Lui Shiong; Ng, Lay Guat; Lau, Weber; Yuen, John Shyi Peng
Abstract : Objective: To evaluate the prognostic values of perinephric fat invasion and renal vein invasion in pT3a renal cell carcinoma, as stand‐alone factors and in combination with tumor size and Fuhrman grade. Methods: Survival data of pT1 and pT2 renal cell carcinomas were analyzed alongside pT3a tumors of similar size bands (pT1 vs pT3a <7 cm, pT2 vs pT3a >7 cm). Patients with adjuvant therapy, positive surgical margins, metastasis or pT3b–pT4 tumors were excluded. Results: No significant baseline demographic differences existed between the groups. Patients with renal vein invasion had larger tumors (median, 7.2 ± 3.0 cm vs 5.5 ± 3.6 cm, P  = 0.039), and were more symptomatic (90.0% vs 61.7%, P  = 0.028) compared with patients with perinephric fat invasion alone. Patients with perinephric fat invasion alone appeared to have better disease‐free survival compared with those with renal vein invasion ( P  = 0.009). Having both perinephric fat invasion and renal vein invasion did not result in a poorer disease‐free survival. pT3a (perinephric fat invasion) tumors <4 cm and 4–7 cm have significantly worse disease‐free survival compared with pT1a and pT1b tumors ( P  < 0.001). Similarly, pT3a (perinephric fat invasion) tumors measuring ≥7 show a trend of poorer disease‐free survival compared with pT2a and pT2b tumors ( P  = 0.267). Disease‐free survival correlated with Fuhrman grading for patients with perinephric fat invasion ( P  = 0.008). In multivariate analysis, the survival curve of pT3a perinephric fat invasion group closely approximates that of pT2 group, whereas survival of the renal vein invasion group was significantly worse than the pT2 and perinephric fat invasion groups ( P  = 0.001). Conclusion: pT3a tumors with perinephric fat invasion appear to have better prognosis than those with renal vein invasion. Further stratification of pT3a renal cell carcinomas with regard to tumor size and Fuhrman grade further enhances the prognostic value in this group.